A different view on ASEAN capital market integration - Robiyanto Robiyanto; Budi Frensidy; Ignatius Roni Setyawan; Andrian Dolfriandra Huruta (Economies, 2021)
Capital market integration has become an interesting research topic nowadays. Many studies have tried to explain this phenomenon using various methods. Here, we used sophisticated methods to explain capital market integration. This study aims to scrutinize the Association of Southeast Asian Nations (ASEAN) capital market integration. This study hopefully can enrich the different views regarding the capital market integration and fill the gap left by previous studies. The data used were the stock price index of the monthly closing data of the capital markets in ASEAN countries during the period of January 1999 to December 2020, obtained from Bloomberg and the Indonesia Stock Exchange. Data in this study were analyzed using the wavelet method. The results indicate that there is a long-term integration in the capital markets of ASEAN countries, and the highest level of integration was in the period during and about a year after the global crisis. Using the spectrum analysis, the results show that during period from 2008 to 2010, the level of integration reached its highest level.
Keywords: G10; G11; G15; 330; ASEAN capital markets; Indonesia Stock Exchange; integration vs. segmentation; spectrum analysis; wavelet analysis